Socioeconomic Characteristics of Small and Medium Sized Dairy Farmers in Punjab : Milk Production, Marketing, & Consumption - Brar, Ravneet Singh; Kaur, Inderpreet; Singh, Varinder Pal; Kaur, Gagandeep (Arthshastra Indian Journal of Economics & Research, 2017)
Livestock is emerging as a driving force in the growth of the agricultural sector of India as it is a major instrument of production for small and medium-sized farmers. Among the livestock, milk constitutes about 68% of the total value of products. Currently, Punjab produces about 7% of the country’s total milk production. The present study attempted to document the important socioeconomic characteristics like education, main occupation, social status, experience in dairying, land ownership status, milk yield, milk production pattern, milk consumption, marketed surplus, and price of milk received by small and medium sized dairy farmers in Punjab. A multistage sampling technique was used to select the sample households. The results of the study revealed that about 52% of the small farmers and 38% medium farmers were educated under the matriculation level. About 70% farmers in the small category and 57% farmers in the medium category had an average experience of more than 15 years in dairying. The daily milk production and marketed surplus were found to be 16.52/L/day and 10.68L/day by small category farmers and 32.69/L/day and 25.74 L/day by medium size category farmers, respectively. The price of milk received by small and medium sized dairy farmers was found to be â‚¹31.92/L and â‚¹33.42/L, respectively for buffalo milk and â‚¹24.36/L and â‚¹25.82/L, respectively for cow milk. About 52% small category farmers and 55% medium category farmers had adopted organized milk marketing channels to sell their produce in the state. The study revealed that there is a huge need of awareness regarding marketing of milk and improvement in pricing policy so that farmers of all categories receive the same price of milk they sell.